1999
DOI: 10.1073/pnas.96.4.1603
|View full text |Cite
|
Sign up to set email alerts
|

Target genes of β-catenin–T cell-factor/lymphoid-enhancer-factor signaling in human colorectal carcinomas

Abstract: Mutations in the adenomatous polyposis coli or ␤-catenin gene lead to cytosolic accumulation of ␤-catenin and, subsequently, to increased transcriptional activity of the ␤-catenin-T cell-factor/lymphoid-enhancer-factor complex. This process seems to play an essential role in the development of most colorectal carcinomas. To identify genes activated by ␤-catenin overexpression, we used colorectal cell lines for transfection with the ␤-catenin gene and searched for genes differentially expressed in the transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
508
0
6

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 750 publications
(539 citation statements)
references
References 47 publications
25
508
0
6
Order By: Relevance
“…In addition, Qiao et al (2004) reported that IGF-1 stimulates the activity of the transcription factor RUNX2, through a PI3K-dependent but Akt-independent signaling pathway. Both Fra-1 and Runx2 are known downstream targets of the Wnt or cat/TCF signaling pathway (Mann et al, 1999;Dong et al, 2006). In this study, we found that insulin stimulates PAK-1 phosphorylation/activation in multiple cancer cell lines and in mouse intestinal tissues on Thr423, a target residue of phosphoinositide-dependent kinase isozyme-1, hence bypassing Akt (King et al, 2000).…”
Section: Discussionmentioning
confidence: 60%
“…In addition, Qiao et al (2004) reported that IGF-1 stimulates the activity of the transcription factor RUNX2, through a PI3K-dependent but Akt-independent signaling pathway. Both Fra-1 and Runx2 are known downstream targets of the Wnt or cat/TCF signaling pathway (Mann et al, 1999;Dong et al, 2006). In this study, we found that insulin stimulates PAK-1 phosphorylation/activation in multiple cancer cell lines and in mouse intestinal tissues on Thr423, a target residue of phosphoinositide-dependent kinase isozyme-1, hence bypassing Akt (King et al, 2000).…”
Section: Discussionmentioning
confidence: 60%
“…Examples include BIRC7, L1CAM, PLAUR and FGF18, which are all downstream targets of Wnt/bcatenin signaling (Mann et al, 1999;Shimokawa et al, 2003;Gavert et al, 2005;Yuan et al, 2007). PLAUR and SERPINE1 are components of the urokinase plasminogen activator system, and the overexpression of these genes has been correlated with a high-grade tumor and poor survival outcomes in RCC (Swiercz et al, 1998;Ohba et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, β-catenin mRNA levels are known to be increased in human primary colorectal cancers and their liver metastases, compared with matched normal-looking tissue [5]. A major regulator of β-catenin expression in human colon cancers is APC, but this is usually viewed from the perspective of β-catenin protein stabilization rather than transcriptional control of β-catenin mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic β-catenin interacts with APC, Axin, glycogen synthase kinase-3β (GSK-3β) and other protein partners, leading to phosphorylation of Ser33, Ser37, Thr41 and Ser45 residues in the N-terminal region of β-catenin, followed by ubiquitination and proteosomal degradation [1][2][3]. In primary human colon tumors and colorectal cancer cell lines, mutations in CTNNB1 substitute one of the four critical Ser/Thr residues and stabilize β-catenin, leading to accumulation of β-catenin/TCF complexes in the nucleus, and activation of downstream target genes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%